Pervasive and recurrent hybridization prevents inbreeding in Europe’s most threatened seabird - Guillem Izquierdo-Arànega; Cristian Cuevas-Caballé; Francesco Giannelli; Josephine R. Paris; Karen Bourgeois; Emiliano Trucchi; Jacob González-Solís; Marta Riutort; Joan Ferrer Obiol; Julio Rozas (Proceedings of the National Academy of Sciences, 2025)
Hybridization is a double-edged sword: While it can erode distinct evolutionary lineages, it can also introduce genetic diversity and adaptive potential into dwindling populations. In the Critically Endangered Balearic shearwater ( Puffinus mauretanicus ), this dilemma is exacerbated by a limited understanding of the extent and consequences of hybridization with the Yelkouan shearwater ( Puffinus yelkouan ). This knowledge gap has limited the scope of science-based conservation strategies to avoid the Balearic shearwater’s imminent extinction. Here, we investigate shearwater hybridization dynamics and their effect on genome-wide diversity in the Balearic shearwater. Divergence dating, demographic modeling, and admixture analyses suggest that these two poorly differentiated shearwater lineages have experienced recurrent episodes of divergence and widespread hybridization during glacial cycles. Selection scans reveal a 500 kb region hosting an adaptive haplotype that potentially underpins interspecific differences in migratory behavior and which has been repeatedly introgressed between the two taxa. Moreover, we show that interspecific gene flow has prevented increases in homozygosity and genetic load, and through forward simulations, we illustrate how it can buffer the negative effects of future population bottlenecks in the Balearic shearwater. Our findings illustrate how introgression can be crucial for maintaining genetic diversity in threatened taxa and highlight the need for considering the protection of hybridization in conservation plans.